2022
DOI: 10.1007/s11356-022-18862-3
|View full text |Cite
|
Sign up to set email alerts
|

High-normal blood pressure (prehypertension) is associated with PM2.5 exposure in young adults

Abstract: We aimed to examine PM 2.5 exposure, blood pressure (SBP and DBP) measurement, hypertension risk factors and to assess the association between PM 2.5 exposure and hypertension among young adults.The mean SBP was 117.78 mmHg, with 11.22% high-normal blood pressure (prehypertension) and 2.51% hypertension (≥ 140 mmHg). DBP was 75.48 mmHg with 26.37% prehypertension and 4.53% hypertension (≥ 90 mmHg). The median PM 2.5 in the past year was 31.79 µg/m 3 , with highest in winter (49.33 µg/m 3 ), followed by spring … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…Our previous study confirmed that chronic PM2.5 exposure was positively associated with SBP, DBP and MAP, and increased the risk of the incidence of hypertension [17]. This conclusion was confirmed by several previous studies [46,47]. However, there were no study to show whether the decreased in ambient PM2.5 concentration has a protective effect on BP growth of children.…”
Section: Discussionsupporting
confidence: 86%
“…Our previous study confirmed that chronic PM2.5 exposure was positively associated with SBP, DBP and MAP, and increased the risk of the incidence of hypertension [17]. This conclusion was confirmed by several previous studies [46,47]. However, there were no study to show whether the decreased in ambient PM2.5 concentration has a protective effect on BP growth of children.…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, frequent outbreaks of severe haze in vast areas of China have drawn widespread public attention [10]. It is estimated that 28% of China's territory (approximately 2.72 million square kilometers) was exposed to severe PM 2.5 pollution (>35 µg/m 3 ) in 2010, including 75% of the 154 Chinese cities with more than one million inhabitants [23,24]. To improve air pollution, the Chinese government has formulated several clean air policies and standards [25], such as the Integrated Emission Standard of Air Pollutants (GB16297-1996), Emission Standard of Air Pollutants of Thermal Power Plants (GB-13223-2011), Ambient Air Quality Standards (GB3095-2012), Technical Regulation on Ambient Air Quality Index (HJ633-2012), Emission Standard of Air Pollutants for Coal-Burning Oil-Burning Gas-Fired Boiler (GB13271-2014), Air Pollution Prevention and Control Action Plan, the 13th Five-Year Plan for Ecological Environmental Protection, and the 14th Five-Year Plan for Ecological Environmental Protection.…”
Section: Introductionmentioning
confidence: 99%
“…This might be a result of environmental expenditures on air quality and to a certain extent the effectiveness of local environmental policies in China, as evidenced by He et al ( 14 ) that they find a 1% increase in environmental expenditure associated with a decrease of 0.0773, 0.0125, 0.0965, and 0.0912% in the air quality index for Beijing, Taiyuan, Chongqing, and Lanzhou cities in China from the period 2007–2015. In the local, levels of PM 2.5 and PM 10 were moderate, which still exceed the annual standard recommended by the world health organization guidelines (WHO IT-1 for PM₂.₅ = 35 μg/m 3 ; WHO IT-2 for PM₁₀ = 50 μg/m 3 ) ( 15 , 16 ). Therefore, mild pollution for the fine particulate matter continuously exists in Jiaxing, which should be supervised, and further studies upon the pollution sources and other pollutant constituents may be alerted.…”
Section: Discussionmentioning
confidence: 86%